2004
DOI: 10.1177/1087057104268749
|View full text |Cite
|
Sign up to set email alerts
|

A Thallium-Sensitive, Fluorescence-Based Assay for Detecting and Characterizing Potassium Channel Modulators in Mammalian Cells

Abstract: Potassium channels have been identified as targets for a large number of therapeutic indications. The ability to use a highthroughput functional assay for the detection and characterization of small-molecule modulators of potassium channels is very desirable. However, present techniques capable of screening very large chemical libraries are limited in terms of data quality, temporal resolution, ease of use, and requirements for specialized instrumentation. To address these issues, the authors have developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
131
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(132 citation statements)
references
References 14 publications
1
131
0
Order By: Relevance
“…Such robust Tl + flux was not surprising given that (1) the cell line was selected for high Kir4.1 expression and function, and (2) Kir4.1 is a ''weak rectifier'' that exhibits a high openstate probability across a broad range of membrane potentials, unlike some voltage-gated K + channels that require depolarization for channel opening and Tl + flux. 37 However, the robustness of Tl + flux raised concerns that the dye would become saturated and fail to report subtle changes in Kir4.1 activity caused by pharmacologically weak modulators in a screen. We reasoned that using a lower Tl + concentration would prevent saturation, increase the sensitivity of the assay, and provide ''headroom'' for identifying activators.…”
Section: Discussionmentioning
confidence: 99%
“…Such robust Tl + flux was not surprising given that (1) the cell line was selected for high Kir4.1 expression and function, and (2) Kir4.1 is a ''weak rectifier'' that exhibits a high openstate probability across a broad range of membrane potentials, unlike some voltage-gated K + channels that require depolarization for channel opening and Tl + flux. 37 However, the robustness of Tl + flux raised concerns that the dye would become saturated and fail to report subtle changes in Kir4.1 activity caused by pharmacologically weak modulators in a screen. We reasoned that using a lower Tl + concentration would prevent saturation, increase the sensitivity of the assay, and provide ''headroom'' for identifying activators.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] The primary approach has involved the use of surrogate ions such as rubidium (Rb þ ) or thallium (Tl þ ), which may be detected by atomic absorption spectrometry 22,23 or fluorescent dyes. 8,10,11 With the advent of automated patch-clamps, 6,[24][25][26][27] it is now possible to consider whether the more direct measurements of channel electrophysiological activity obtained from the automated patch-clamp justifies its higher implementation cost in high-throughput screens. It is therefore important to obtain more specific and quantitative information to assess the cost and benefit comparatives between assays employing electrophysiological methods versus surrogate ion flux measurements.…”
mentioning
confidence: 99%
“…The former is usually carried out by taking advantage of fluorescent dyes that selectively bind to the targeted ions. 8,10,11 The latter is often based on the membrane potential changes following ion fluxes. 12,13 Using surrogate ionic fluxes, several large HTS campaigns have been recently described in published reports 14,15 and in a public database (PubChem AIDs 1456, 1511, 1672, 1918, 2156, and 2239).…”
mentioning
confidence: 99%
“…Compound 13k was subsequently dosed at 3 mg/kg, infusion over 30 min in the anesthetized rabbit pharmacodynamic model, and a robust increase of 21 ± 2.8% in AERP was observed without significant effect on VERP, QTc (Delta QTc cf, 13 ± 4.2 ms), or BP (Table 2). 17 We were encouraged by the robust increase in AERP in this model; however, in the rat VERP studies, a significant level of brain penetration was observed (3 mg/kg i.v. 5 min infusion, 10 min post-end of infusion C plasma 3.1 ± 0.3 μM, brain exposure 8.8 ± 1.6 μM.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%